Epitaxial Growth of III-Nitride Compounds Computational Approach (Springer Series in Materials Science,, 2018)
This book presents extensive information on the mechanisms of epitaxial growth in III-nitride compounds, drawing on a state-of-the-art computational approach that combines ab initio calculations, empirical interatomic potentials, and Monte Carlo simulations to do so. It discusses important theoretical aspects of surface structures and elemental growth processes during the epitaxial growth of III-nitride compounds. In addition, it discusses advanced fundamental structural and electronic properties, surface structures, fundamental growth processes and novel behavior of thin films in III-nitride semiconductors. As such, it will appeal to all researchers, engineers and graduate students seeking detailed information on crystal growth and its application to III-nitride compounds.